NILAI RISK PRIORITY NUMBER (RPN) DALAM PENGOLAHAN MINYAK KELAPA SAWIT DENGAN METODE RELIABILITY CENTERED MAINTENANCE DI PT X - Masdania Zurairah; Hendra Tongam Maraden Purba; Rahmad Rezeki (Jurnal Cakrawala Ilmiah, 2024)
Research has been carried out regarding the risk priority value of Namber. Where obtained RPN 240 on the diaphragm and RPN 56 on Replenishing. So the highest damage is to the diaphragm.